Application Agile Governance in Improving Food Security for Commodity Rice Bandung City Government, West Java - Alifatu Lela Mazidah; Khaerul Umam; Faizal Pikri (Social Impact Journal, 2022)
Food security is still an issue that needs attention because it affects all aspects for both the government and the community. In order to increase the effort of food security especially rice commodities, Bandung City provides the best through new programmes and innovations, namely ATM beras and Buruan SAE. The research objective to be achieved in this study is to determine whether the city of Bandung has implemented Agile Governance either through innovation or programs that have been made. This study used descriptive qualitative method. Data was collected by observation, interviews, and literature studies. The result of this research is that the city of Bandung has implemented the concept of Agile Governance in overcoming the food security of its rice commodity. Although there are still some shortcomings in the implementation of the basic principles of Agile Governance itself.